Justice Negotiations for Women: Divorce Cases Due to Domestic Violence in Religious Courts - Bani Syarif Maula; Ariyanti , Vivi (Jurnal Hukum Islam, 2022)
This study is to analyze the resistance of Muslim women to gender hierarchy in the family through khulu' (divorce) which is caused by acts of domestic violence. This empirical juridical research uses sample data from the Central Java Religious Court. The sample is selected based on the highest number of divorce cases in Indonesia, especially those caused by acts of domestic violence. The results of the study show that the religious court is the place most visited by muslim women in an effort to negotiate justice to stop domestic violence experienced by wives because Religious Courts are considered to provide strength to challenge the gender hierarchy in the household. Divorce initiated by the wife allows women to become active agents in determining marital status. However, Religious Court Judges do not use domestic violence as an excuse to decide on divorce cases. In his decision, the judge only mentioned the reason for the divorce because of the constant fights between husband and wife